Reconocimiento y configuración del derecho al ambiente en Argentina : Algunos antecedentes relevantes - Pinto, Mauricio (2016)
In Argentina, the Environment is now recognized as an object of constitutionally guaranteed right and, thus, it is susceptible to judicial protection. Its recognition process and its content configuration were evolutionarily analyzed through a contextual analysis of its reception as a legal precedent and its influence on the current legal paradigm. The aim of this work was to determine the effects of judicial activism on the recognition and the configuration of the right to the environment as a prerogative of collective action. It was hypothesized that regulations are the result of praetorian innovations acting as legal sources. It was possible to conclude that the regulatory recognition of the right to the environment is based on previous court decisions which have continued shaping its profile from a collective action perspective. As a result, evidence assessment, the consistency principle, and the res judicata effect have been innovated.